When things aren't going right, go left - Colagiovanni, Marc (Orchard Books, an imprint of Scholastic, Inc., 2023)
"Told through creative language play, and with depth and whimsy, this picture book reminds readers of their own agency and the power they have to direct their own path. Marc Colagiovanni's lyrical text and Peter H. Reynolds's stunning art create an enduring message of strength and perseverance that is both universal and personal, and one that readers will be drawn to over and over again. This first of two new picture books created in collaboration with Marc and Peter will inspire, affirm, and reassure readers at key milestone moments in every young reader's life. When Things Aren't Going Right, Go Left makes an inspiring graduation gift as well as a must-have, uplifting read sure to bring positivity to all who read it and remind us that even when nothing is going right... we can always choose to go left."--Publisher marketing